ANALYSIS LOCAL WISDOM OF RICE PLANTS IN NAGARI SIMPURUIK SUBDISTRICT SUNGAI TARAB TANAH DATAR REGENCY WEST SUMATERA PROVINCE - Arif Zurdi Busenda; Eri Sayamar; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study was conducted in Nagari Sungai Tarab Simpuruik Tanah Datar, Nagari Simpuruik been divided into two Jorong namely Jorong Simpuruik and Sijangek. This study was conducted to identify local wisdom that never existed and still exists today, as well as analyzing the local wisdom that are environmentally friendly and any strategy in maintaining indigenous rice crops. The author's purpose which is to collect old culture that has been lost and record any culture that has been lost, thereby maintaining local knowledge of the area. The method used is qualitative the research methods used to examine the condition of natural objects. The sampling technique using snowball sampling techniques in sequence to obtain the saturation point of a question. By way of in-depth interviews with respondents and record it in the form of voice recorder that uses a questionnaire that has been made previously. Local knowledge is a form habits of the people who uphold the norms and values ​​of their culture, they run it for generations to his son and nephew in running their daily lives. In this study there is local wisdom that are still running, even though the procedures taught were not overly done. But they still carry out such wisdom. Keywords: Local Wisdom. Environment. Strategy Local Wisdom